TATA KELOLA REKAM MEDIS BERBASIS TEKNOLOGI INFORMASI UNTUK LAPORAN INDEKS PENYAKIT POLI JANTUNG DI RSUD AL - IHSAN - Hazni, Silva Novial (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
At this time, technology is generally used to help the completion of work to be easier, faster and more accurate. One of the uses of technology in medical record management is an important part of success in implementing good corporate governance which aims to ensure that health service organizations are responsible for continuously improving the quality of their services and guaranteeing the provision of services with high standards by creating an environment where excellent service. Utilization of visual basic information technology in medical management which is intended to facilitate officers in the process of collecting data related to heart disease up to the process of analyzing and reporting. The research method used is a quantitative method with a descriptive approach. With data collection techniques in the form of observation, interviews and literature and using the waterfall system development method. The purpose of this study is that with this disease index data system, it is hoped that it will make it easier to make reports and can speed up the process of making disease index reports every month for reporting to the hospital management department.